Batman. The doom that came in Gotham [videorecording (Blu-Ray)] - Ricci, Jase; Mignola, Mike (SDS, 2023)
The chilling and bizarre DC Elseworlds story is a mash-up of the world of Batman and the cosmic-horror fiction of H.P. Lovecraft, creator of the Cthulhu mythos. Returning from a decade-long voyage of discovery, Bruce Wayne returns to Gotham City, where his parents fell victim to the knife of a madman 20 years earlier. On his journey, Bruce has taken on an international trio of orphaned street kids, whom Batman fans will recognize as various iterations of Robin. During a deadly Arctic encounter, the Penguin informs Bruce that a doomsday cult is planning Gotham₂s destruction. Bruce must now return home and take on the mantle of Batman. But when this man of science discovers he faces not criminals and crazies but actual ancient magic, fiery demons, and interdimensional Old Gods, can he retain his sanity?